Development of hybrid SVM-FA, DT-FA and MLR-FA models to predict the flexural strength (FS) of recycled concrete - Wang, Qiang; Zhou, Mengmeng (Frontiers in Materials, 2023)
Recycled concrete from construction waste used as road material is a current sustainable approach. To provide feasible suggestions for civil engineers to prepare recycled concrete with high flexural strength (FS) for the road pavement, the present study proposed three hybrid machine learning models by combining support vector machine (SVM), decision tree (DT) and multiple linear regression (MLR) with the Firefly algorithm (FA) for the computational optimization, named as SVM-FA, DT-FA, and MLR-FA models, respectively. Effective water-cement ratio (WC), aggregate-cement ratio (AC), RCA replacement (RCA), nominal maximum RCA size (NMR), nominal maximum NA size (NMN), bulk density of RCA (BDR), bulk density of NA (BDN), water absorption of RCA (WAR) and water absorption of NA (WAN) were employed as the input variables. To determine the predicting results of varying hybrid models, root mean square error (RMSE) and correlation coefficient (R) were used as performance indexes. The results showed that the SVM-FA demonstrated the highest R values and the lowest RMSE values, and the fitting effect of the predicted values and the actual values of the FS of recycled concrete is the best. All the above analysis proving that the SVM optimized by FA hyperparameter has the highest prediction accuracy. The results of sensitivity analysis showed that WC has the most significant influence on the FS of recycled concrete, while RCA has the weakest influence on the FS, which should be noticed when engineers apply recycled concrete to road design in the future.